2022
DOI: 10.3389/fphy.2022.940980
|View full text |Cite
|
Sign up to set email alerts
|

Do Active Nematic Self-Mixing Dynamics Help Growing Bacterial Colonies to Maintain Local Genetic Diversity?

Abstract: Recent studies have shown that packings of cells, both eukaryotic cellular tissues and growing or swarming bacterial colonies, can often be understood as active nematic fluids. A key property of volume-conserving active nematic model systems is chaotic self-mixing characterized by motile topological defects. However, for active nematics driven by growth rather than motility, less is understood about mixing and defect motion. Mixing could affect evolutionary outcomes in bacterial colonies by counteracting the t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 62 publications
0
6
0
Order By: Relevance
“…However, as the open domains show, the decoupling seems to be an intrinsic feature of near-perfect orientational order. Therefore, it could also be relevant for the emergent dynamics on other length scales, such as the growth and break-up of microdomains in expanding colonies, which are highly ordered patches at intermediate length scales [ 19 , 21 , 40 ]. Moreover, the decoupling is closely related to the buckling instability, as it allows the build-up of unequal stresses in the first place [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, as the open domains show, the decoupling seems to be an intrinsic feature of near-perfect orientational order. Therefore, it could also be relevant for the emergent dynamics on other length scales, such as the growth and break-up of microdomains in expanding colonies, which are highly ordered patches at intermediate length scales [ 19 , 21 , 40 ]. Moreover, the decoupling is closely related to the buckling instability, as it allows the build-up of unequal stresses in the first place [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…To this end, it is worth mentioning that, in a similar context of nonmotile bacterial colonies, a recent study by Schwarzendahl et al 55 identified +1/2 and À1/2 topological journal is © The Royal Society of Chemistry 2024 defects. [56][57][58] Their methodology involved computations of the nematic tensorial orientation field, mapping it to continuum fields using a smoothing function and identifying these defects through integration and clustering algorithms.…”
Section: Cell Length Variation and Nematic Ordering In Growing Bacter...mentioning
confidence: 97%
“…For further details regarding calculating the orientational autocorrelation, please refer to the ESI. †To this end, it is worth mentioning that, in a similar context of nonmotile bacterial colonies, a recent study by Schwarzendahl et al55 identified +1/2 and À1/2 topological…”
mentioning
confidence: 99%
“…47,48 Moreover, simulations of growing bacterial colonies revealed that the cells mix more efficiently when they are elongated. 49 It is known that bacteria can change their aspect ratio depending on the conditions. 8,50 It is also possible to control the aspect ratio of bacteria in experiments, which revealed that the vorticity in swarming bacteria is maximized for an intermediate aspect ratio.…”
Section: Aligning Parametermentioning
confidence: 99%